Influence of Different Taste Feed Additives on Feed Intake and Growth Performance in Growing Goats - Naveen, P.; Kour, Harneet; Malik, Raman; Naliyapara, Hardik; Gabbur, Anil; Rana, Parul; Goyal, Amandeep (Flavour and fragrance journal, 2025)
The present study was carried out to evaluate the influence of different taste feed additives on feed intake and growth performance in Alpine × Beetal growing goats. For this, a 90‐day growth trial was conducted on 36 growing goats of 3–4 months age which were divided into six groups of six animals each. Animals in all groups were fed individually to meet the requirement for both maintenance and growth as per ICAR 2013. Individual taste feed additives were added in their concentrate mixture of total mixed ration (TMR) as food‐grade sucrose (sweet) at the rate of 75 g/kg DM (SWE), NaCl (salt) at the rate of 15 g/kg DM (SAL), food‐grade citric acid (sour) at the rate of 10 g/kg DM (SOU), urea (bitter) at the rate of 5 g/kg DM (BIT) and food‐grade monosodium glutamate (umami) at the rate of 10 g/kg DM (UMA). The study revealed significantly higher ( p < 0.01) average dry matter intake (DMI) (kg/day) in SWE (0.541 ± 0.034) and SAL (0.560 ± 0.041) groups compared to CON (0.476 ± 0.039). Average daily body weight gain (g/d/animal) was significantly higher ( p < 0.01) in sweet and salt taste‐supplemented groups compared to control. Body measurements including heart girth, withers height, body length and hip height were similar among six treatments. Feed conversion efficiency (kg live weight gain/100 kg DMI) and feed conversion ratio (kg DMI/kg live weight gain) were unaffected due to taste supplementation. While supplementation of sweet taste increased the digestibility of NDF and ADF, sweet‐ and salt‐supplemented groups increased DCP as well as TDN intake. It was concluded that addition of sweet and salt taste in TMR had a positive impact on feed intake and growth performance in growing goats.